Child Development three to five [videorecording] - Conrad, Tim.; Finzen, Susan; Meridian Education Corporation (Bloomington, Ill. Meridian Education Corporation, 1990)
Overviews the major physical, emotional, and intellectual stages of development for children from three to five years old. Included are interviews with a child psychologist and parents. Also included is an exploration of how children at this stage become self-aware and begin socialization.
Keywords: Child development